Eksplorasi Kemampuan Pemecahan Masalah Siswa SMA Dalam menyelesaikan Masalah Eksponensial - Qothrotun Nada; Purwanto Prasetyo Aji (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
The purpose of this research is to describe the ability of solving mathematical problems to be able to solve problems related to the mathematical abilities of high school level students. The subjects of this study were 37 students of class X SMA. The method used in collecting research data is to give tests in the form of description questions to three students who have studied exponential material in the category of low mathematical ability, moderate mathematical ability and high mathematical ability by fulfilling 4 conditions: (1) understand the problem, where students can identify problems by showing information that is known, asked, as well as the completeness of the required elements. (2) Planning for completion, where students are able to determine the formula or initial method of completion, can carry out investigations to solve problems. (3) Carry out planning, where students carry out plans by carrying out settlements according to the planned steps. As well as (4) checking the process and results, where students re-check the results of the completion to ensure the work steps are in accordance with the procedure. After that the interviews were conducted with the aim of seeing the reasons for the mistakes made by students. The results showed that students with high mathematical ability had fulfilled the four stages of Polya well in solving problems related to exponential material. Â Tujuan penelitian ini adalah mendeskripsikan kemampuan pemecahan masalah matematis untuk dapat menyelesaikan masalah yang berkaitan dengan kemampuan matematis peserta didik tingkat SMA. Subjek penelitian ini adalah siswa kelas X SMA yang berjumlah 37 siswa. Cara yang dilakukan dalam pengambilan data penelitian adalah dengan memberikan tes berupa soal uraian kepada tiga peserta didik yang telah mempelajari materi eksponensial yang berkategori kemampuan matematis rendah, kemampuan matematis sedang dan kemampuan matematis tinggi dengan memenuhi 4 syarat: (1) memahami masalah, dimana peserta didik dapat mengidentifikasi permasalahan dengan menunjukan informasi yang diketahui, ditanya, serta kelengkapan unsur yang dibutuhkan. (2) Merencanakan penyelesaian, dimana peserta didik mampu menentukan rumus atau cara awal penyelesaian, dapat melakukan penyelidikan untuk pemecahan masalah. (3) Melaksanakan perencanaanan, dimana peserta didik melaksanakan rencana dengan melakukan penyelesaian sesuai langkah yang direncanakan. Serta (4) memeriksa proses dan hasil, dimana peserta didik memeriksa kembali hasil penyelesaian untuk memastikan langkah pengerjaan sesuai dengan prosedur.. Setelah itu wawancara dilakukan degan tujuan untuk melihat alasan terjadinya kesalahan yang dilakukan oleh peserta didik. Hasil penelitian didapatkan peserta didik dengan kemampuan matematis yang tinggi telah memenuhi empat tahapan Polya dengan baik dalam menyelesaikan masalah terkait materi eksponensial.